Biosorptive removal of lead by lentil husk. Issue 2 (June 2015) - Basu, Mousumi; Guha, Arun K.; Ray, Lalitagauri
Highlights: Lentil husk has been used as a sorbent for removal of lead. Sorption is optimum at pH 5.0 and the process is well defined by Langmuir isotherm model. The process gets completed within 60 min following pseudo-second order rate kinetics. Adsorption is further confirmed by SEM, EDAX and FTIR analyses. Abstract: Lentil husk an agricultural waste was found to be a promising low cost adsorbent for removal of lead and showed maximum adsorption potential among all other agricultural wastes tested. Different physico-chemical parameters were found to influence the adsorption process. Lead uptake capacity of lentil husk ( q max ) was 81.43 mg g −1 at optimized pH (5.0) and temperature (30 °C) with an initial metal ion concentration of 250 mg L −1 . Adsorption process was well interpreted by Langmuir isotherm model. Kinetic study showed sorption was very fast at initial stage and equilibrium was reached within 60 min following pseudo second order rate model. Scanning electron microscopy (SEM), energy dispersive X-ray analysis (EDAX) and Fourier transform infrared spectroscopy (FTIR) further confirmed the sorption of lead. Chemical modification of functional groups revealed both hydroxyl and carboxyl groups played crucial role in binding process. The concerned biomass was capable of removing lead from actual industrial effluent.